George Lewis : A Jazzman from New Orleans. - Bethell, Tom (UC Press voices revived., 2022)
George Lewis, one of the great traditional jazz clarinetists, was born in 1900 at about the same time that jazz itself first appeared in New Orleans. And by the time he died, on the last day of 1968, New Orleans jazz had pretty much run its course, too. By then a jazz museum stood on Bourbon Street, and a cultural center was under construction where Globe Hall had Stood. Lewis's life thus paralleled that of New Orleans jazz, and in his later years hew as the b.